Storytelling Pesan Dakwah dalam Novel Surga Yang Tak Dirindukan 2 Karya Asma Nadia - Dewi, Yuli Sartika Yuli; Gunawan, Asep; Pesha, Indry Nirma Yunizul (Universitas Ibn Khaldun Bogor, 2025)
Literary work (novel) is one of the concrete manifestations of the human imagination to express thoughts, views, inspiration and convey messages. Storytelling in the novel has a role as a carrier of the journey of a story to make it more interesting. Bringing roles in real life which are then arranged into stories, based on well-structured values ​​to express messages. This study used the Library Research method, which is research by searching data based on pre-existing written works. The research aims to understand how the storytelling and da'wah messages are in the novel Heaven that is not missed 2, by using Teun a Van Djik discourse analysis. The elements of analysis presented by Van Djik are divided into three levels, namely macro structure, super structure and micro structure. These elements are used to obtain a global meaning from a media text. This research is also accompanied by primary sources, namely the novel Heaven that is not missed 2, as well as secondary sources as a complement, namely books, research works, articles, and so on. So that in the end, the research found storytelling that was quite good, seen from the themes that were built in the novel Heaven that was not missed 2. Such as themes about Islam, kinship, experience, humanity, and inspiration. One of the very dominant characteristics of a novel is being able to change the outlook on life or the way of thinking of its readers. The novel is used as a medium for preaching, because basically the activity of preaching changes a person's behavior for the better. It was also found in the research that various da'wah messages in the novel include relationships with God and relationships with humans. Among them, recommendations for doing good, avoiding adultery, maintaining sincerity, recommendations for repentance, the nature of polygamy, covering genitalia, and accepting God's destiny.